A315 FREQUENCY AND PREDICTORS OF FASTING ORDERS IN INPATIENTS WITH ULCERATIVE COLITIS: THE AUDIT OF DIET ORDERS - ULCERATIVE COLITIS (ADORE-UC) STUDY. (1st March 2018) - Gallinger, Z; Nguyen, G C; Steinhart, A; Fortinsky, K J; Pivovarov, K; Rumman, A
Abstract: Background: Current clinical practice guidelines suggest that ulcerative colitis (UC) patients admitted due to a disease flare should be offered a normal diet or enteral nutrition unless such a diet is not tolerated. Despite this recommendation, concerns about iatrogenic malnutrition from unjustified NPO or clear liquid diet (CLD) orders exist. Aims: We aim to describe the frequency and audit the appropriateness of NPO and CLD orders among hospitalized UC patients and identify predictors of unjustified fasting. Methods: We conducted a retrospective cohort study of all UC patients who were admitted to the gastroenterology (GI) service or the general internal medicine (GIM) service at an academic hospital between January 2009 and December 2014. The frequency and duration of bowel rest orders and the number of meals missed because of these orders were assessed. Bowel rest orders were considered justified if the patient had intractable nausea or vomiting, pancreatitis, bowel obstruction, toxic megacolon or were awaiting endoscopy, or if alternative enteral or parenteral nutrition was provided. Patients with unjustified fasting orders were identified and the number of missed meal opportunities was measured. A logistic regression model was used to assess predictors of unjustified fasting in admitted UC patients. Results: A total of 187 admissions in 158 UC patients were identified during the study period and included in the final analysis. The majority of the admissions were under the GI service (148/187, 79.1%). The mean age at admission was 35.0 years (standard deviation [SD] = 15) and 83/158 (52.5%) were female. The median length of stay was 8 days (interquartile range [IQR] = 4 – 12). Registered dietician consultation was obtained in only 32 admissions (17.1%), and admission weight was recorded in only 68 (36.4%) admissions. A total of 252 NPO or CF dietary orders were encountered in 142 admissions (75.9%). Of those, 112 orders were unjustified (44%). On average, patients with unjustified NPO or CF orders spent 3 days on an NPO or CF diet, which corresponded to a mean of 10 missed meals. Significant predictors of unjustified NPO or CF dietary orders were: NPO or CF diet ordered on admission [odds ratio, OR = 12.9, 95% confidence interval, 4.78–34.9]; admission to non-GI service [11.7, 95% CI 2.63–52.2], and lack of inpatient prednisone or biologics [3.4, 95% CI 1.4–11.6]. Conclusions: There is a high burden of prolonged bowel rest among hospitalized UC patients. Further studies are needed to assess the nutritional impact of prolonged bowel rest on UC patients. Our findings also suggest that targeted interventions are needed to decrease the frequency of inappropriate bowel rest among hospitalized UC patients. Funding Agencies: None